A study on the removal of osteosynthetic materials following surgical treatment for maxillofacial fractures - NUKATA, Junichiro; UCHIDA, Hiroshi; MATUMOTO, Riki; KANO, Yasuyuki; OHMAE, Masatoshi; FUJISHIRO, Hiromi; ADACHI, Minoru; SAKUDA, Masayoshi; OHTA, Yoshiyuki (Japanese Journal of Oral and Maxillofacial Surgery, 1996)
Ninety-seven patients who had undergone internal fixation for maxillofacial fractures were examined with respect to the removal of osteosynthetic materials. All patients were scheduled to undergo removal of implant materials, but 16 patients refused. Among these patients, 64 % refused because they did not wont to undergo a second operation, 18% because they feared facial nerve palsy, 18 % because they feared an operation scar. Osteosynthetic materials were removed in 67 % of patients more than 40 years of ago and 87% of patients less than 40 years. Midface osteosynthetic materials were removed in 92% of male patients and 71% of female patients. Mandibular osteosynthetic materials were removed in 97% of patients treated with an intraoral approach and 63% of patients treated with an extraoral approach. To facilitate the removal of midface osteosynthetic materials, operation should be done with an unmarked skin incision. To increase the removal rate of mandibular osteosynthetic Materials, operation should be done with an intraoral approach, if possible.